Cryopreservation of Spin-Dried Mammalian Cells - Chakraborty, Nilay; Menze, Michael A.; Malsam, Jason; Aksan, Alptekin; Hand, Steven C.; Toner, Mehmet (PLOS ONE, 2011)
This study reports an alternative approach to achieve vitrification where cells are pre-desiccated prior to cooling to cryogenic temperatures for storage. Chinese Hamster Ovary (CHO) cells suspended in a trehalose solution were rapidly and uniformly desiccated to a low moisture content (<0.12 g of water per g of dry weight) using a spin-drying technique. Trehalose was also introduced into the cells using a high-capacity trehalose transporter (TRET1). Fourier Transform Infrared Spectroscopy (FTIR) was used to examine the uniformity of water concentration distribution in the spin-dried samples. 62% of the cells were shown to survive spin-drying in the presence of trehalose following immediate rehydration. The spin-dried samples were stored in liquid nitrogen (LN2) at a vitrified state. It was shown that following re-warming to room temperature and re-hydration with a fully complemented cell culture medium, 51% of the spin-dried and vitrified cells survived and demonstrated normal growth characteristics. Spin-drying is a novel strategy that can be used to improve cryopreservation outcome by promoting rapid vitrification.